Exome Sequencing Identifies the Extremely Rare ITGAV and FN1 Variants in Early Onset Inflammatory Bowel Disease Patients - Al-Numan, Huda Husain; Jan, Rana Mohammed; Al-Saud, Najla bint Saud; Rashidi, Omran M.; Alrayes, Nuha Mohammad; Alsufyani, Hadeel A.; Mujalli, Abdulrahman; Shaik, Noor Ahmad; Mosli, Mahmoud Hisham; Elango, Ramu; Saadah, Omar I.; Banaganapalli, Babajan (Frontiers in Pediatrics, 2022)
Background Molecular diagnosis of early onset inflammatory bowel disease (IBD) is very important for adopting suitable treatment strategies. Owing to the sparse data available, this study aims to identify the molecular basis of early onset IBD in Arab patients. Methods A consanguineous Arab family with monozygotic twins presenting early onset IBD was screened by whole exome sequencing (WES). The variants functional characterization was performed by a series of computational biology methods. The IBD variants were further screened in in-house whole exome data of 100 Saudi cohorts ensure their rare prevalence in the population. Results Genetic screening has identified the digenic autosomal recessive mode of inheritance of ITGAV (G58V) and FN1 (G313V) variants in IBD twins with early onset IBD. Findings from pathogenicity predictions, stability and molecular dynamics have confirmed the deleterious nature of both variants on structural features of the corresponding proteins. Functional biology data suggested that both genes show abundant expression in gastrointestinal tract and immune organs, involved in immune cell restriction, regulation of different immune related pathways. Data from knockout mouse models for ITGAV gene has revealed that the dysregulated expression of this gene impacts intestinal immune homeostasis. The defective ITGAV and FN1 involved in integrin pathway, are likely to induce intestinal inflammation by disturbing immune homeostasis. Conclusions Our findings provide novel insights into the molecular etiology of pediatric onset IBD and may likely pave way in developing genomic medicine.